American journal of physical anthropology : official publication of the American Association of Physical Anthropologists - American Association of Physical Anthropologists; Stini, William A. (New York : Alan R. Liss, Inc., 1983)
"The American Journal of Physical Anthropology is designed for the prompt publication of original and significant articles on human evolution and variation, including primate morphology, physiology, genetics, adaptation, growth, development, and behavior present and past."
Seasonal variation in pre- and postpartum maternal body measurements and infant birth weights Adair, Linda S. and Pollitt, Ernesto
Includes bibliographical references.
in English.
Keywords: Physical anthropology -- Periodicals. Societies. Serials; Antiquities, Prehistoric; Prehistoric peoples